Effect of Ti addition on the quasicrystalline phase formation and indentation characteristics of Zr69.5Al7.5Cu 12Ni11 alloy - Singh D.; Yadav T.P.; Mandal R.K.; Tiwari R.S.; Srivastava O.N. (My University, 2025)
The crystallisation behaviour and indentation characteristics of melt-spun (Zr69.5Al7.5Cu12Ni11) 100-xTix (x = 0-16 at. %) metallic glasses was investigated. Differential scanning calorimetry traces revealed changes in crystallisation behaviour with addition of Ti. Formation of a nanoquasicrystalline phase by annealing the glass was found up to x = 12. Further increase of Ti content gives rise to formation of a Zr 2Ni-type crystalline phase. In addition to this, the size of nanoquasicrystals decreases with increasing addition of Ti. The load-dependent hardness behaviour of the metallic glasses and nanoquasicrystal-glass composites is reported in detail. The value of the yield strength of the materials was estimated with the help of hardness values based on the empirical correlations available in literature. The formation of shear bands around the indentation periphery was observed. It was found that microstructural and morphological changes alter the indentation characteristics of glasses as well as composites formed after controlled crystallisation. © 2011 Taylor & Francis.